SISTEM INFORMASI MANAJEMEN PENGELOLAAN INTERNET UNIVERSITAS MA CHUNG DENGAN PENGGUNAAN MIKROTIK API SERVICES DENGAN AUTENTIFIKASI O365 - Krisna, Gathan Fitra; Kurniawan, Yudhi (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2023)
Efficient and safe management of internet access is a primary requirement in a network environment that continues to develop. In an effort to minimize problems such as network overload, trial users, and MAC address manipulation, this research proposes an internet hotspot authentication system based on Microsoft Office 365 accounts. This system is intended for Ma Chung University to carry out internet management. By leveraging Microsoft and Mikrotik APIs, users can log in to the hotspot network using their O365 credentials, ensuring account validity and increasing access security. This system is designed to integrate Microsoft authentication services with Mikrotik network infrastructure, enabling more centralized and reliable authentication. The Mikrotik API is used to manage user access in real-time, while the Microsoft API provides control over user credentials and validity. The result is a more effective internet management information system, which not only reduces network load but also reduces the use of trial accounts and unauthorized MAC address changes. This system can also monitor active users connected to the internet. The implementation of this system is expected to provide a scalable and secure solution for managing internet access, by utilizing API technology to improve user experience and operational efficiency.